Uncertainty due to infectious diseases and forecastability of the realized variance of United States real estate investment trusts: A note - Matteo Bonato; Oğuzhan Çepni; Rangan Gupta; Christian Pierdzioch (International Review of Finance, 2021)
We examine the forecasting power of a daily newspaper-based index of uncertainty associated with infectious diseases (EMVID) for real estate investment trusts (REITs) realized market variance of the United States (US) via the heterogeneous autoregressive realized volatility (HAR-RV) model. Our results show that the EMVID index improves the forecast accuracy of realized variance of REITs at short-, medium-, and long-run horizons in a statistically significant manner, with the result being robust to the inclusion of additional controls (leverage, realized jumps, skewness, and kurtosis) capturing extreme market movements, and also carries over to 10 sub-sectors of the US REITs market. Our results have important portfolio implications for investors during the current period of unprecedented levels of uncertainty resulting from the outbreak of COVID-19.
Keywords: 330; forecasting; infectious diseases; realized variance; REITs; uncertainty